Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbantuan Media Audiovisual Terhadap Kemampuan Menulis Teks Eksplanasi Pada Kelas VIII SMP Amir Hamzah Medan - Nada Despriyanti Sitanggang; M. Joharis Lubis (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
The purpose of this study was to determine the effect of using the Cooperative Learning Model Type Teams Games Tournament (TGT) Aided by Audiovisual Media on the Ability to Write Explanatory Texts in Class VIII of SMP Amir Hamzah Medan on the ability to write explanatory texts in Class VIII Students of SMP Amir Hamzah Medan . The population in this study were all class VIII students of Amir Hamzah Private Middle School Medan in the 2022/2023 academic year, totaling 47 people consisting of 2 classes, while the sample used was 25 students, determined by random sampling technique. The research method used is a quantitative experimental method. The instrument in this study was a writing test of explanatory text which was assessed based on the content, text structure, and language conventions of the explanatory text. The average score obtained by students before applying learning with the Cooperative learning model of the Teams Games Tournament (TGT) type assisted by audiovisual media was 61.68, while the average value obtained by students after using the assisted Teams Games Tournament (TGT) type of Cooperative learning model audiovisual media, namely 79.68. So, it can be concluded that the test scores after applying the Cooperative learning model of the Teams Games Tournament (TGT) type assisted by audiovisual media are higher than before. The results of data analysis in testing the hypothesis show that tcount = 4.28, then looking at the t table, the significance level is 5%, and df = N – 1 = 25 – 1 = 24, it is obtained ttable = 1.71. Because the obtained tcount is greater than ttable, namely 4.28> 1.71, the null hypothesis (Ho) is rejected and the alternative hypothesis Ha is accepted.